DAMPAK KEBIJAKAN DIGITALISASI PENDIDIKAN TERHADAP KUALITAS PEMBELAJARAN DI SMA NEGERI 2 DUSUN HILIR - Ani, Fatrahul; Suriansyah, Ahmad; Purwanti, Ratna (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
This study aims to analyze the impact of the education digitalization policy on the quality of learning at SMA Negeri 2 Dusun Hilir. The background of this study is based on the importance of educational transformation along with the rapid development of technology in the Industrial Revolution 4.0 era. Education digitalization is seen as a strategy to improve the quality of learning, equal access, and efficiency of administration and learning methods. This study uses a qualitative approach with data collection techniques through interviews, and is analyzed through the process of data reduction, data presentation, and drawing conclusions. The results of the study indicate that the education digitalization policy has a positive impact on the learning process, including through easy access to information, the emergence of new, more innovative and flexible learning methods. However, digitalization also has negative impacts such as the digital competency gap between teachers and students, the potential for misuse of technology, data security threats, and decreased direct social interaction. At SMA Negeri 2 Dusun Hilir, the success of implementing this policy is influenced by several supporting factors such as adequate technological infrastructure, teacher training, and school management support. Meanwhile, inhibiting factors include low digital literacy of some teachers and students, limited access to devices and the internet, and lack of supervision of technology use.